Pengaruh Kompetensi Sumber Daya Manusia, Pemanfaatan Teknologi Informasi Dan Pengendalian Intern Terhadap Keandalan Laporan Keuangan - David Prasetyo; Mulyanto Nugroho (Universitas Katolik Widya Karya Malang, 2024)
The study aimed to assess how the utilization of information technology, internal control, and HR competencies affect the reliability of financial statements. Through the use of questionnaires, a